Inhibition of CO2 Corrosion of 1030 Carbon Steel Beneath Sand-deposits - Pandarinathan, V.; Lepkova, Katerina; Gubner, Rolf (NACE, 2011)
The performance of three corrosion inhibitors was investigated at 1030 carbon steel surfaces in the presence and absence of a sand deposit. Potentiodynamic measurements showed that the inhibition efficiency to mitigate corrosion reactions decreases in the presence of sand deposit. In contrary, the inhibitor performance was found to increase with longer exposure time of the steel to the corrosive media, at sand deposited surfaces. The differences between the steels corroded with and without sand deposit in the presence of an inhibitor were confirmed using both potentiostatic polarisation technique and scanning electron microscopy. The inhibition activity of the studied compounds in mitigating under-deposit corrosion of carbon steel has been discussed.